2010
DOI: 10.1111/j.1744-6163.2010.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Gatekeeper Suicide-Awareness Program for Nursing Personnel

Abstract: We suggest that nursing personnel's continuing education include a training program for suicide prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 21 publications
1
24
0
4
Order By: Relevance
“…Healthcare providers are susceptible to the same biases toward persons with mental illness that are still common in general society, as well as additional issues related to frustration or discomfort with, or dislike or misunderstanding of, suicidal patients . It is important to acknowledge these biases and knowledge gaps when designing provider education programs or care protocols, and focused training programs have been shown to have positive short‐term effects on provider attitudes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare providers are susceptible to the same biases toward persons with mental illness that are still common in general society, as well as additional issues related to frustration or discomfort with, or dislike or misunderstanding of, suicidal patients . It is important to acknowledge these biases and knowledge gaps when designing provider education programs or care protocols, and focused training programs have been shown to have positive short‐term effects on provider attitudes …”
Section: Discussionmentioning
confidence: 99%
“…[11,19,[24][25][26] It is important to acknowledge these biases and knowledge gaps when designing provider education programs or care protocols, and focused training programs have been shown to have positive short-term effects on provider attitudes. [11,27,28] A minority of providers in this multisite sample reported screening most or all patients for SI; of note, none of the included sites had universal screening protocols in place at the time of the study. Far more nurses than physicians reported screening patients, which may reflect traditional models of care with triage nurse assessments followed by more focused physician and primary nurse evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, after a discussion about the "correct" answers-which established which person was most likely to die by suicide-participants in the study demonstrated improved ability to recognize risk factors on a subsequent assessment. Several additional studies also indicate the potential effect of educational intervention on understanding signs of risk (Lamis, Underwood, & D'Amore, 2016;Pisano, Cross, Watts, & Conner, 2011;Tsai, Lin, Chang, Yu, & Chou, 2011). Although the public seems to benefit from learning about common warning signs in order to identify them more readily (e.g., Lamis et al, 2016;Madson & Vas, 2003;Pisani et al, 2011;Tsai et al, 2011), research suggests that the "IS PATH WARM?"…”
mentioning
confidence: 99%
“…Our findings have been confirmed by numerous studies of suicide prevention training, namely, that non-continuous training is not sufficient in itself to achieve a steady and long-term reduction in suicide rates. Rather, there is a demonstrable need for consistent, repeated, and standardized training in suicide prevention that covers various aspects of suicidal behaviour [1114]. We further believe that since there is no consistent, repeated, and standardized training on suicide prevention at present, Lithuania will not achieve a meaningful degree of preventative efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Most research shows that in order to achieve a steady and long-term reduction in the suicide rate, non-continuous training is not enough, and there is a need for continual, repeated, and standardized suicide prevention training. More effort should be directed towards evaluating the existing methods of training healthcare providers in this field, including making further practical recommendations and improvements, allowing for the rational allocation of resources, and instituting the long-term and systematic training of healthcare professionals [1014]. …”
Section: Introductionmentioning
confidence: 99%